Budaya Keunggulan Akademik di Sekolah Dasar Negeri Bintoro 5 Demak - Negoro, Sriwari; Egar, Ngasbun; Yuliejantiningsih, Yovitha (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
The focus of this research is 1) collective reliability in the Culture of Academic Excellence at Bintoro 5 Public Elementary School, Demak, 2) staff trust in parents and students in the Culture of Academic Excellence at Bintoro 5 Public Elementary School, Demak, and 3) academic emphasis in the Culture of Academic Excellence at Bintoro 5 Public Elementary School, Demak. The approach used in this research is qualitative descriptive, which is a research method based on positivist philosophy to investigate the natural conditions of the object, where the researcher is the key instrument, and data sources consist of primary and secondary data. Data sampling is done purposively and snowball sampling is used. Data collection techniques involve data triangulation, and data analysis is inductive/qualitative in nature. The research findings indicate that Collective Reliability Culture at Bintoro 5 Demak Elementary School is built through teachers' competency mastery experiences, students' personal experiences, social persuasion, and emotional generation. Meanwhile, staff trust in students and parents is formed through committee involvement, accountability, and close collaboration. On the other hand, academic emphasis is reflected through collaborative work practices, commitment to improving teaching, high expectations, and high academic standards. Recommendations for Bintoro 5 Demak Elementary School involve workload management, monitoring of positive emotional impact, emphasis on consistency and teaching strategies, strengthening of committee and collaboration programs, involvement of other staff, and innovation in awards. Additionally, strengthening collaboration and involvement of other staff, as well as innovative curriculum development, are suggested to enhance trust and support academic emphasis. The positive implications of the academic excellence culture on academic achievement can serve as a foundation for education policymakers. The active participation of the entire school community in providing contributions and input is crucial. With an understanding of these implications, Bintoro 5 Demak Elementary School can continually improve their practices and culture to achieve sustainable academic excellence, serving as a guide for other schools seeking to enhance the quality of education and academic emphasis. Keywords: culture, academic optimism culture, staff trust, collective reliability, academic emphasis.